Mechanically Stable Dynamic Urea Bond‐Based Crosslinked Polymer Blend with Tunable Self‐Healable and Physical Properties. Issue 1 (15th January 2021) - Zhou, Zhongqun; Chen, Shenye; Li, Weichen; He, Junjie; Yu, Caili; Zhang, Faai
Abstract : Front Cover : In article number 2000527 by Faai Zhang and co‐workers, a crosslinked polymer blend based on a urethane‒arcylate system with a combination of reversibly noncovalent intrachain and interchain hydrogen bonds and dynamically covalent urea bonds is developed through a facile in situ photoinduced copolymerization. The materials exhibit rapid self‐healing at mild conditions (70 °C, 30 min), extreme toughness (≈34.76 MJ m −3 ), high tensile strength, superior stretchability, long‐term stability, recyclability, and weldability.